Comparison of dynamic balance test scores of young female volleyball and soccer players - Adigüzel, N. S.; Koç, M. (International Journal of Applied Exercise Physiology, 2020)
Flexibility and balance are two main fitness components which are commonly prescribed to enhance athletic performance and reduce the risk of injury (1). However it has been not well documented in the literature that how athletes from different sports branches perform on these components. This study proposed to compare the scores of young female soccer and volleyball players in the Star Excursion Balance Test (SEBT) which is designed to measure flexibility and dynamic postural control or balance. Twenty-one female student-athletes aged 15-17 years participated in the study. The sample included soccer (n=10) and volleyball (n=11) players who attend a sports high school in Turkey and compete at national and international level. Meanage, height and weight of the participants were 15.9±0.3 years, 161.5±6.1 cm, and 50.8±4.5 kg, respectively, for soccer players, and 16.5±0.7 years, 165.1±7.8 cm, and 55.9±7.7 kg, respectively, for volleyball players. Normalized reach distances (leg length percentages) were compared for anterolateral (AL), anterior (ANT), anteromedial (AM), medial (MD), posteromedial (PM), posterior (PO), posterolateral (PL), and lateral (LAT) directions using the Independent Samples T-TEST. The soccer players reached farther than the volleyball players on the right leg in the PL and LAT directions, and on the left leg in the MD and PO directions (p<0.05) while there were no significant differences in forward lunge with right and left leg distances between the groups (p<0.05). We can conclude that volleyball and soccer players may differ in terms of dynamic balance in the SEBT. The findings of this study may also contribute to the literature to reveal to establish reference values for SEBT performance in adolescent population.